Paediatric torsion of the paradidymis - Matthew J. Marino; Roy M. Kimble (Elsevier, 2018)
Torsion of the paradidymis is an uncommon diagnosis made in children after scrotal exploration. It usually presents as a painful hemiscrotum warranting exploration to exclude torsion of the testis, though it may be painless. We present a case of torsion of the paradidymis in a four-year-old boy presenting with a painful hemiscrotum and review similar cases in the literature. Keywords: Paradidymis, Torsion, Child